IMPLEMENT A TWO-STEP SCREENING FOR COGNITIVE IMPAIRMENT IN PRIMARY CARE SERVICES IN NORTHERN PORTUGAL. (11th November 2018) - Paul, C; Teixeira, L; Santos, P; O'Caoimh, R
Abstract: Background:Progression from mild cognitive impairment (MCI) characterized by demonstrable cognitive decline insufficient to impair activities, to dementia may be slowed through non-pharmacological approaches, particularly if cognitive impairment is identified early. Objective:To evaluate General Practitioners (GPs) clinical perception of cognitive impairment in older community-dwellers as part of a fast-track, two-step screening and referral primary care pathway using the new Quick Mild Cognitive Impairment (Qmci) screen –Portuguese translation. Methods:GPs (N=285) across 55 healthcare units in Northern Portugal were recruited. Based on GPs knowledge, all patients aged ≥65 were screened for mental health concerns using the 'Mental Health' subtest of the Risk Instrument for Screening in the Community (RISC), a dichotomous Yes/No question. Using a stratified probability sample, considering gender, age and geographical area as strata, a subset of those screening positive were assessed by independent researchers and classified using the Global Deterioration Scale (GDS). The Qmci screen was scored for GDS scores ≥1. Results:Of the 7, 298 available, 2, 734 (37.4%) adults screened positive on the RISC of which 572 were further assessed. Of these, 11.8% refused to participate and a further 13.4% were excluded based on the GDS. Of the remaining 436 with a GDS ≥1 94.3% screened positive for cognitive impairment (Qmci cut-off:58/100), 93% (n=119/128) with probable MCI (cut-off:65/100). Conclusion:The Qmci-Portuguese version appears a useful short (5mins) screen in primary care, corroborating the clinical perception of GPs. Based on these results we suggest further study is required to confirm if two-step screening for cognitive decline is feasible and acceptable in primary care.